2016
DOI: 10.1093/brain/aww175
|View full text |Cite
|
Sign up to set email alerts
|

Visual dysfunction in Parkinson’s disease

Abstract: Visual symptoms are frequently reported in Parkinson’s disease. Weil et al.. relate visual changes to underlying brain regions, and consider mechanisms for visual hallucinations. They examine links between visual changes and other features of Parkinson’s disease and discuss the role of visual dysfunction as a marker of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
301
4
9

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(323 citation statements)
references
References 233 publications
(301 reference statements)
9
301
4
9
Order By: Relevance
“…Given that there was a significant difference between the visual acuity scores at 100% contrast in both groups, it is possible that this reflects impaired color perception besides contrast sensitivity. Abnormalities in color vision are well known in PD . One possible explanation for no significant difference observed for yellow at low contrast could simply be the marked difficulty of seeing a lighter color (yellow) against a white background, as evidenced by the extremely low score in the control group (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…Given that there was a significant difference between the visual acuity scores at 100% contrast in both groups, it is possible that this reflects impaired color perception besides contrast sensitivity. Abnormalities in color vision are well known in PD . One possible explanation for no significant difference observed for yellow at low contrast could simply be the marked difficulty of seeing a lighter color (yellow) against a white background, as evidenced by the extremely low score in the control group (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…However, the relationship between color vision disturbances and motor disturbances is controversial and not confirmed. Some studies have reported that CV deteriorated along with the progress of the disease [13,14]. Other studies have demonstrated that there was no correlation between the degree of CV in PD and the dopaminergic nigral degeneration examined by single-photon emission tomography, which proves that the origin of visual disorders in PD is extranigral [15].…”
Section: IIImentioning
confidence: 99%
“…Farnsworth's multicolor tests with 15, 85 and 100 tones are widely used abroad. Studies based on these tests have revealed color discrimination disorders, mostly in the blue-green spectrum, in moderate and severe stages of PD, also a relationship has been found between the CV disturbances and deteriorating visuospatial orientation and cognitive functions [13]. However, the relationship between color vision disturbances and motor disturbances is controversial and not confirmed.…”
Section: IIImentioning
confidence: 99%
“…Retinal dopaminergic neuronal degeneration and alpha synuclein deposition are seen in the brainstem, occipital and parietal cortices, which can explain dysfunction with eye movement, visual perception and visuospatial ability [56].…”
Section: Non Motor Featuresmentioning
confidence: 99%